Batal Demi Hukum: Poligami Tanpa Persetujuan Isteri: Studi Kasus POLDA Provinsi Maluku Utara - Muhammad Zaber Wahid; Baharuddin Hi. M.A Hi. Abdullah (Program Studi Hukum Keluarga dan Hukum Ekonomi Syariah, Program Pascasarjana Institut Agama Islam Negeri (IAIN) Ternate, 2021)
Marriage Law in Indonesia adheres to the principle of Monogamy. That is, a husband can only have a wife. But in the applicable law, polygamy is possible on several conditions including a wife's license and authorized by the court. In practice, many polygamy practices carried out without the wife's knowledge are even done